Bradycardia during laparoscopic surgeries: A cross-sectional study - Gautam, Binod; Maharjan, Ashmita; Ghimire, Suson (Journal of Kathmandu Medical College, 2020)
Background: Bradycardia occurring during laparoscopic surgery potentially leads to cardiac arrest and adverse outcomes. Apart from the vagal reflex for its genesis, the knowledge on frequency and risk factors is limited. Objectives: To identify the bradycardia frequency and time points for its occurrence during laparoscopic surgeries. Methodology: In this hospital-based cross-sectional study, anaesthesia-related incident reports on bradycardia were collected from January to December 2019. Bradycardias (heart rate less than 60/minute) that occurred during laparoscopic surgeries were analyzed to characterize patient factors, the time point for occurrence, circumstantial events, management strategies, and outcomes. Results: Among 801 laparoscopic surgeries, 28 (3.4%) bradycardic incidents were identified, with one progressing to cardiac arrest. All bradycardias occurred in 26 patients undergoing laparoscopic cholecystectomy under general anaesthesia, with two patients each experiencing two bradycardic episodes. The mean patient age was 45 (±16.3) years and 17 (65.3%) were women. Fifteen (57.6%) patients had no co-morbidity. Controlled hypertension and hypothyroidism co-existed in seven (26.9%) and three (11.5%) cases respectively. Bradycardia occurred once each (3.5%) during laryngoscopy and endotracheal intubation. Six (21.4%) and twenty (71.4%) bradycardias respectively occurred before and during pneumoperitoneum. The mean of minimum heart rates was 43 (±8.8) per minute. Anticholinergics were administered in 25 (89.2%) incidents. Stopping surgery and pneumoperitoneum deflation included other major management strategies. The cardiac arrest case received chest compressions and adrenaline. Surgery resumed in all cases without adversity. Conclusion: Bradycardia occurs during laparoscopic surgery, more frequently during pneumoperitoneum and in healthy and younger females. Immediate cessation of surgical stimuli and atropine administration possibly prevent bradycardia from progressing to cardiac arrest.